Acceptability of Unsweetened Small-quantity Lipid-based Nutrient Supplements in Mexico Among 7 to 24 Month-old Children and Their Caregivers: A Formative Research Study (P10-046-19). (13th June 2019) - Okronipa, Harriet; Miranda, Selene; Rawlinson, Cloe; Olvera, Armando G; Gonzalez, Wendy; Bonvecchio, Anabelle
Abstract: Objectives: Lipid-based nutrient supplements (LNS) have the potential to improve micronutrient status, growth and development of children. While the sweetened version of the supplement has been found to be acceptable, the acceptability of unsweetened LNS is unknown. The study was conducted to examine the acceptability of unsweetened small-quantity LNS (SQ-LNS) among Mexican children and their caregivers. Methods: Eligible caregivers of 7 to 24 mo-old children ( n  = 13) participated in an SQ-LNS tasting session at a hospital in a semi-urban area of the state of Morelos, Mexico. Using a 3-point hedonic scale, they rated the organoleptic characteristics of SQ-LNS (alone and mixed with food) and their willingness to feed it to their child. Subsequently, a focus group discussion was conducted to further explore caregivers' experiences and perceptions about the supplement. Feeding sessions were carried out in caregivers' homes, during which children ( n  = 8) were fed a meal consisting of SQ-LNS (20 g) mixed with a local complementary food (36 g). The amount (g) of meal consumed by the children was measured. Results: Most women ( n  = 12) liked the smell of the supplement and more than half ( n  = 8) liked the appearance. However, less than a quarter liked the taste ( n  = 3) and texture ( n  = 2) and more than half ( n  = 8) perceived that their child would dislike it. Irrespective of caregiver's perception regarding the supplement, a majority ( n  = 9) reported they would be willing to feed it to their children mostly because of its nutritional content and health benefits. Caregivers reported that they would prefer to mix the supplement with food before feeding to child and would try different strategies including mixing the supplement with foods that are commonly eaten at home that the child likes. When caregivers rated LNS mixed with food, results showed that more than half liked the taste ( n  = 8) and perceived that their child would like it ( n  = 9). On average, children consumed 23.8 ± 19.2 g of the meal (equivalent to a proportion of 42 ± 34%). Conclusions: Although the taste of unsweetened SQ-LNS was not largely accepted, caregivers expressed their willingness to feed the supplement to their children using different strategies. The use of unsweetened SQ-LNS in future studies in this population may be acceptable. Funding Sources: The study was funded by the Government of Canada, as part of the Business Platform for Nutrition Research hosted by the Global Alliance for Improved Nutrition.